2018
DOI: 10.1214/18-aap1410
|View full text |Cite
|
Sign up to set email alerts
|

Tail measure and spectral tail process of regularly varying time series

Abstract: The goal of this paper is an exhaustive investigation of the link between the tail measure of a regularly varying time series and its spectral tail process, independently introduced in Owada and Samorodnitsky (2012) and Basrak and Segers (2009). Our main result is to prove in an abstract framework that there is a one to one correspondance between these two objets, and given one of them to show that it is always possible to build a time series of which it will be the tail measure or the spectral tail process. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(92 citation statements)
references
References 26 publications
2
90
0
Order By: Relevance
“…valid again for all measurable functionals F as above, see e.g., [2,19]. We note in passing that with the same arguments as in [19] it can be shown that (2.6) is equivalent to the so-called time-change formula proven in [2] for multivariate regularly varying rf's.…”
Section: General Max-stable Xmentioning
confidence: 81%
See 4 more Smart Citations
“…valid again for all measurable functionals F as above, see e.g., [2,19]. We note in passing that with the same arguments as in [19] it can be shown that (2.6) is equivalent to the so-called time-change formula proven in [2] for multivariate regularly varying rf's.…”
Section: General Max-stable Xmentioning
confidence: 81%
“…valid again for all measurable functionals F as above, see e.g., [2,19]. We note in passing that with the same arguments as in [19] it can be shown that (2.6) is equivalent to the so-called time-change formula proven in [2] for multivariate regularly varying rf's. Next, since for stationary X we have that (2.2) holds, then in view of [2,19] X is a multivariate regularly varying rf and Y is the so-called tail rf of X, whereas Θ is the so-called spectral tail rf.…”
Section: General Max-stable Xmentioning
confidence: 81%
See 3 more Smart Citations